The impact of a vegetarian diet on thyroid health – a review of current literature - Palacz, Bartosz; Trela , Katarzyna; Kubiś , Natalia Marianna; Wrona, Julia Anna; Polus , Aleksander; Perz, Wiktor; Teper, Maria Magdalena; Korolchuk , Anhelina; Gluzicka, Anna; Matyas, Anna; Piotrowski, Jędrzej (Journal of Education, Health and Sport, 2026)
Background: Thyroid dysfunction is one of the most common endocrine disorders and represents an important public health issue. Its etiology is multifactorial and includes genetic, immunological, environmental, and dietary factors. A vegetarian diet, rich in plant-based foods, provides bioactive compounds with antioxidant and anti-inflammatory properties that may influence immune regulation. However, poorly balanced vegetarian diets may result in deficiencies of nutrients essential for thyroid function, including iodine, selenium, and vitamin B12. Aim: This study aims to review current scientific evidence on the effects of a vegetarian diet on thyroid function, focusing on potential benefits, risks, and the role of supplementation. Materials and methods: A narrative literature review was conducted using publications from PubMed, Scopus, and Web of Science databases published between 2010 and 2025. Articles addressing vegetarian diets, thyroid function, autoimmune thyroid diseases, and micronutrient supplementation were analyzed. Results: Evidence suggests that a vegetarian diet may have both beneficial and adverse effects on thyroid health. Benefits include higher intake of antioxidants, lower body weight, and a potentially reduced risk of hyperthyroidism. Conversely, vegetarians show a higher risk of deficiencies in iodine, selenium, vitamin B12, and omega-3 fatty acids, which may contribute to hypothyroidism and exacerbate autoimmune thyroid diseases. Regular monitoring and targeted supplementation are therefore recommended. Conclusions: A well-planned vegetarian diet can support thyroid health when appropriate supplementation is ensured. Increased awareness of potential nutrient deficiencies, particularly in individuals with thyroid disorders and in pregnant women, is essential. Further research is needed to establish optimal dietary strategies for thyroid health in vegetarian populations.